The prevalence and characterisation of Escherichia coli on fresh produce from selected farms, retail outlets and markets in the Western Cape - Jordaan, Marlize (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc Food Science)--Stellenbosch University, 2013.